Adsorption/Desorption of Cationic-Hydrophobic Peptides on Zwitterionic Lipid Bilayer Is Associated with the Possibility of Proton Transfer - Lea Pašalić; Andreja Jakas; Barbara Pem; Danijela Bakarić (MDPI AG, 2023)
Cell-penetrating peptides (CPPs) are short peptides built up from dominantly cationic and hydrophobic amino acid residues with a distinguished ability to pass through the cell membrane. Due to the possibility of linking and delivering the appropriate cargo at the desired location, CPPs are considered an economic and less invasive alternative to antibiotics. Besides knowing that their membrane passage mechanism is a complex function of CPP chemical composition, the ionic strength of the solution, and the membrane composition, all other details on how they penetrate cell membranes are rather vague. The aim of this study is to elucidate the ad(de)sorption of arginine-/lysine- and phenylalanine-rich peptides on a lipid membrane composed of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) lipids. DSC and temperature-dependent UV-Vis measurements confirmed the impact of the adsorbed peptides on thermotropic properties of DPPC, but in an inconclusive way. On the other hand, FTIR spectra acquired at 30 °C and 50 °C (when DPPC lipids are found in the gel and fluid phase, respectively) unambiguously confirmed the proton transfer between particular titratable functional groups of R5F2/K5F2 that highly depend on their immediate surroundings (DPPC or a phosphate buffer). Molecular dynamic simulations showed that both peptides may adsorb onto the bilayer, but K5F2 desorbs more easily and favors the solvent, while R5F2 remains attached. The results obtained in this work highlight the importance of proton transfer in the design of CPPs with their desired cargo, as its charge and composition dictates the possibility of entering the cell.